The Economics of Tobacco in Egypt : A New Analysis of Demand - Nassar, Heba (World Bank, Washington, DC, 2013)
This study examines the economics of tobacco production and demand in Egypt. It reviews previous studies of demand for cigarettes in Egypt, consumption tends in Egypt, in the context of regional trends, and the data on tobacco-attributable diseases in Egypt. It describes the structure and trends in cigarette production in Egypt, and the level of imports and exports. Part 2 uses household expenditure survey data from 1995/96 and 1999/2000 to look at levels and trends in household expenditures on cigarettes and other tobacco products, by income level, education, rural/urban residence, works status and occupation. The same data are used to analyze the demand for cigarettes and other tobacco products in Egypt, estimating expenditure (income) and price elasticities for the various population subgroups. The results are comparable to similar empirical estimates from other countries. The elasticities are used to simulate the likely effect on consumption of a rise in the price of cigarettes. The results of a survey of knowledge, attitudes and behaviors with respect to tobacco use of 559 university students are reported. Finally, Egypt's tobacco control policies, activities and plans are described.